Divergent Landowners' Expectations May Hinder the Uptake of a Forest Certificate Trading Scheme. Issue 3 (28th September 2017) - Giannichi, Marta Lisli; Dallimer, Martin; Baker, Timothy R.; Mitchell, Gordon; Bernasconi, Paula; Ziv, Guy
Abstract: A major challenge to reduce forest loss in the tropics is to incentivize conservation on private land in agricultural settings. Engaging private landowners in conservation schemes is particularly important along deforestation frontiers, such as in the southern Brazilian Amazon. While we know much about what motivates landowners to participate as providers, or sellers, of conservation schemes, understanding what motivates landowners who act as buyers, that is, those who require land to meet conservation obligations, remains lacking. Here we identify viewpoints of sellers and buyers of an emerging forest certificate trading scheme in Brazil and quantify the compatibility of their views to examine potential barriers to trade. Sellers and buyers could be divided into three groups, but only one group in each case was positive about participating in the scheme. A key concern of buyers was the desire for establishing contracts with a long duration; in contrast, price was a key issue for sellers. Addressing these concerns by defining minimum contract lengths and restricting the spatial scale of transactions will be essential if this scheme is to realise its potential to reduce rates of deforestation.